Understanding and solving environmental problems in the 21st century : toward a new, integrated hard problem science - Costanza, Robert; Jrgensen, Sven Erik, 1934- (Elsevier, 2002)
The aim of this book is to encourage integration of the natural and social sciences with the policy and design-making community, and thereby develop a deeper understanding of complex environmental problems. Its fundamental themes are: & bull; integrated modeling and assessment & bull; complex, adaptive, hierarchical systems & bull; ecosystem services & bull; science and decision-making & bull; ecosystem health and human health & bull; quality of life and the distribution of wealth and resources. This book will act as a state of the art assessment of integrated environmental science and its relation to real world problem solving. It is aimed not only at the academic community, but also as a sourcebook for managers, policy makers, and the informed public. It deals both with the state of the science and the level of consensus among scientists on key environmental issues. The concepts underlying this book were developed at the 2nd EcoSummit workshop held in Halifax, Nova Scotia, June, 2000, with active participation from all delegates, and attempts to present their collective view.